Evaluasi Waktu Tempuh Kendaraan Dan Kinerja Ruas Jalan Rute Sicincinbukittinggi Saat Penerapan Sistem Satu Arah Pada Musim Mudik Lebaran 2024 - Satria, Fachrian; Yossyafra; Yosritzal , Yosritzal (Syntax Literate, 2025)
West Sumatra stands as one of the regional divisions with a high number of Lebaran homecoming travelers, as many residents migrate to various parts of Indonesia. This leads to an increase in vehicle volume entering West Sumatra during the Lebaran period. The West Sumatra Provincial Government, in collaboration with the West Sumatra Police Department, implemented a One Way System traffic management scheme on the Sicincin–Bukittinggi road segment during the 2024 Lebaran season, from three days before (H-3) until three days after (H+3) Lebaran. This study aims to evaluate vehicle travel time and road segment performance on the Sicincin–Bukittinggi route during the One Way System implementation and to provide route recommendations for the system. The evaluation results show that the VC Ratio before and after Lebaran ranged from 0.37 to 0.82 and 0.62 to 0.91, respectively. The route via Padang Panjang offers an average travel time savings of approximately 10 minutes, while the route via Malalak increases travel time by around 5 minutes. Therefore, the One Way System through Padang Panjang is recommended, along with caution for traffic surges after Lebaran.